PENGARUH SOSIALISASI POLITIK TERHADAP TINGKAT PARTISIPASI POLITIK MASYARAKAT KECAMATAN SENAPELAN PADA PILKADA KOTA PEKANBARU 2017 - Wardani, Widia Kusuma; Erlinda, Sri; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research was motivated by the high level of political participation in Senapelan sub-district, that is 60.9%. In reality, few people are willing to participate in politics. However, in contrast to Senapelan sub-district, there were a high participation. So the researcher want to see how the socialization obtained by the community resulting in high levels of participation. The formulation of the problem in this research is how is the political socialization, what is the level of political participation, is there any political socialization agent that has the most influence on political participation, and is there any influence between political socialization on the level of political participation. The population in this study was the total number of voters in the elections Pekanbaru 2017 amounted to 21,648 and the sample in this study was 100 respondents. The instruments of data collection were questionnaire, interview, observation, and documentation. Data analysis with quantitative descriptive. The results showed that the calculation of the percentage of respondents as a whole, the answer is not good as much as 23.21% is in the range 0% -25% for political socialization. While political participation is at the apolitical level because it is in the range 51% -100%. The most influential agent of participation is the family, because the value of Standardized Coefficient Beta owned by the family is greater than the other agents. Furthermore, there is an influence of political socialization on the level of political participation because the score of Fcount is higher than Ftable.Keywords : Influence, Political Socialization, Political Participation